LEADERSHIP AND TECHNOLOGICAL-ENVIRONMENTAL LITERACY: THE SCIENCE CLUB WITHIN THE FULL-TIME EDUCATION PROGRAM IN HUMAITÁ, AMAZONAS - Alves, Rodrigo Henrique Risso Aires; Pereira, Mariana Arinana Canuto; Araújo, Estephanie Guimarães; Martins, Wilson Ramos; da Silva, Diana Lima; dos Santos, Miquele Araújo; Oliveira, Ludimila Souza; Ponce, Ana Paula Silva (Seven Editora, 2026)
Pedagogical management in full-time institutions within the Amazon region faces the critical challenge of converting extended school hours into a period of emancipatory education. This study analyzes the potential of the Science Club, based at the Integrated Center for Complementary Activities (CIAC) in Humaitá-AM, as an ecosystem for technological-environmental literacy. The investigation problematizes the invisibility of environmental stressors in daily school life—such as noise pollution and inadequate waste management—proposing digital instrumentation as a means for diagnosis and intervention. Grounded in the principles of Scientific Literacy and Maker Culture, this action-research describes a pedagogical engineering process in which elementary students utilize open-source hardware and microcontrollers to transmute subjective sensory perceptions into measurable empirical data. The methodological path integrated cycles of virtual simulation, C++ programming, and the assembly of sonometric and sanitary automation devices. The results demonstrate that the materialization of technological artifacts promotes an epistemological transition, shifting the student from a technology consumer to an active diagnostician of their territory. The study concludes that the symbiosis between instrumental accuracy and ethical purpose enhances the full-time curriculum, consolidating youth leadership and providing technical support for the management of collective well-being in the Amazonian context.